Navigating the volatility of higher education : anthropological and policy perspectives - Foster, Brian L.; Graham, Steven W.; Donaldson, Joe F. (Education policy in practice., 2018)
Applied Anthropology provides a new perspective on today's higher education environment. Volatile and unpredictable forces affect research and instruction across many sectors and levels, and global dynamics are among the strongest drivers of change. Further, within American higher education, daunting complexity and multiple layers of activity weave a rich tapestry of environment, structure, and culture.This book provides three complementary anthropological perspectives as a framework for analyzing the ground-shifting changes underway in higher education - the higher education mindset, political and policy perspectives, and instruction and learning. These domains intersect with many operational dimensions of higher education - research, health care, athletics, economic development, fiscal management, planning, and faculty roles/challenges - another way of framing the complexity of the situation we are addressing. Book chapters also provide a set of implications for higher education policy. The book concludes with a vision of next steps in research and practice to further anthropology's contribution to higher education policy and practice.The intended audience includes both academic and professionals--e.g., faculty and students in departments of higher education, anthropology, and education policy. Higher education leaders, administrators, governing board members, and many others will find the book helpful in providing insight into today's challenges. The book will also be of use to professionals outside higher education who work on policy issues, on meeting the needs of employers, and on preparing students for careers in public service.